Acculturation Coalesce Between Islamic Leadership with Minangkabau Local Wisdom - R. Iqbal Robbie; Andhika Rahmat Saputra; Yans Nur Afifah (Karsa: Journal of Social and Islamic Culture, 2021)
The Minangkabau community has a long history of Islamic culture. This historical fact is assisted by the Minangkabau natural Tambo which contains philosophy, goals, ideals, normativity, regulations, and proverbs that presuppose consensus as to the goals of society. The purpose of this study, using the perspective of Jurgen Habermas, which is based on the theory of communicative action, the researcher is helped in studying the forms of deliberation from the democratic system of the Minangkabau natural society. Qualitative research is the research method used. The critical paradigm is the chosen solution. In this study, which is combined with the concepts of shari'a associated with communication theory, Habermas’ critical hermeneutic theory will be used. The results of this study show the discursive decision-making process in the Nagari, which is then questioned with the lareh dualism that gave birth to the Tuah sakato democracy. Then from a long study related to how the deliberation process in the Minang realm has the potential to be epistemic in the post-secular era, the researchers also found that the IKM regional organizations as developers of these potentials were outside the realm and had an impact on the Minang realm itself. The results of this study can trigger further researchers to participate in cultural studies and human resources related to the importance of epistemic attitudes in the post-secular era.